2003
DOI: 10.1097/01.mp.0000066800.44492.1b
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptors (α and β) and 17β-Hydroxysteroid Dehydrogenase Type 1 and 2 in Thyroid Disorders: Possible In Situ Estrogen Synthesis and Actions

Abstract: Both epidemiological and experimental findings suggest the possible roles of sex steroids in the pathogenesis and/or development of various human thyroid disorders. In this study, we evaluated the expression of estrogen receptors (ER) ␣ and ␤ in normal thyroid glands (N ‫؍‬ 25; female: n ‫؍‬ 13, male: n ‫؍‬ 10, unknown: n ‫؍‬ 2) ranging in age from fetus to adult. Furthermore, using immunohistochemistry, we investigated the expression of ER␣ and ␤ in 206 cases of thyroid disorders, including 24 adenomatous goi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 24 publications
2
56
0
3
Order By: Relevance
“…15,16 Furthermore, ER is expressed in a wide subset of carcinomas, including those primary to the endometrium and ovary, but also in ''unexpected'' sites, such as papillary carcinomas of the thyroid 17,18 and adnexal tumors of the skin. 19,20 Most important from a diagnostic standpoint, a significant number of primary lung adenocarcinomas (approximately 10%-20%) can also show positive immunostaining, although in general these tumors show only focal ER expression.…”
Section: Breast Cancer Markersmentioning
confidence: 99%
“…15,16 Furthermore, ER is expressed in a wide subset of carcinomas, including those primary to the endometrium and ovary, but also in ''unexpected'' sites, such as papillary carcinomas of the thyroid 17,18 and adnexal tumors of the skin. 19,20 Most important from a diagnostic standpoint, a significant number of primary lung adenocarcinomas (approximately 10%-20%) can also show positive immunostaining, although in general these tumors show only focal ER expression.…”
Section: Breast Cancer Markersmentioning
confidence: 99%
“…It could be explained in two ways. First, human thyroid gland has both intracrine or paracrine estrogen responsiveness and in situ estrogen synthesis [19,20] as uterine fibroid has [21]. In previous studies about uterine fibroids, systemic E2 levels showed no difference between subjects with uterine fibroids and without [22][23][24].…”
Section: Acknowledgementmentioning
confidence: 99%
“…Тому залишаєть-ся дискутабельним питання, чому в низці випад-ків диспластичні процеси поширюються не на всю молочну залозу, а тільки на певні ділянки. За да-ними дослідників [4,5], це пов'язано з дефіцитом гестагенів і чутливістю рецепторів до естрадіолу та прогестерону. Гормональний дисбаланс сприяє морфофункціональній перебудові молочних залоз, Практикуючому ендокринологу /To Practicing Endocrinologists/ і в частини жінок в умовах активації рецепторного апарата молочних залоз формуються патологічні зміни [6,7].…”
Section: вступunclassified